KORELASI PEMAHAMAN MATA KULIAH LOGIKA MATEMATIKA DENGAN SOFTWARE GEOGEBRA - Harizahayu Harizahayu; Ferdinan Rinaldo Tampubolon (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
This study investigated the use of a free GeoGebra application, where the ability of a GeoGebra software application had the potential to simplify and help the teaching and learning process in the informatics management study program, Medan State Polytechnic. The focus of this research was the incorporation of conventional method-based teaching, namely using the assistance of writing instruments such as pencils, pens, and paper when describing the Venn diagram in mathematical logic courses with the help of the GeoGebra application which made it easier for students to drew circles and determine the slices and combinations on the Venn diagram. The resulted of this study were obtained from the scores of student assignments and the results of interviews conducted online with the number of respondents consisting of 44 students who successfully uploaded assignments through the SIPADI application. The value analysis obtained was compiled into tables then processed using the SPSS application using the pair test and linearity test. Based on the output obtained, it was known that the GeoGebra value obtained the average value of learning outcomes or the mean of 75.9773, while for the average learning outcomes using conventional methods or the mean of 68.9091. The number of respondents or students who took the test amounted to 44 people, Std. Deviation for GeoGebra method was 5.800092 and conventional method was 5.56909, and Std. Error Means. Based on the results of descriptive statistical tests, the average value of the GeoGebra method > conventional method was 75.9773> 68.9091, so descriptively there was an average difference between the GeoGebra method and the conventional method.